Pengaruh Kegiatan Bina Keluarga Remaja Terhadap Akhlak Remaja Di Kelurahan Bukit Gado-Gado Kota Padang - Debi Yandrizal; Martin Kustati; Nana Sepriyanti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to determine the influence of youth family development activities in developing youth in KB Pesona Indah Bukit Gado-Gado Village, South Padang District. The type of research is qualitative, data collection techniques are observation, interviews and documentation. Research informants, Head of Bukit Gado-Gado Village, Youth Family Development Group, Parents who have Teenagers and Adolescents. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this research reveal that the role of the BKR Group in developing teenagers is carried out through 3 (three) stages of the role, namely counseling, coaching and guidance to parents of teenagers which is then continued to teenagers. Keywords: Building Teen Families, Teenage Morals, Gado-Gado Hill, Padang City